370 Safety of oncologic surgery without preoperative covid-19 testing in asymptomatic patients. (4th December 2020) - Orhan, Nazlı; Akgor, Utku; Ozgul, Nejat; Salman, Mehmet Coskun; Gultekin, Murat
Abstract : Introduction/Background: Novel Coronavirus Disease (COVID-19) pandemic has a significant impact on healthcare services. Non-emergent surgeries are being restricted since medical facilities are mostly occupied by or reserved for COVID-19 patients. However, postponing oncologic surgeries may have significant effects on survival. Also, many reports were published regarding the safety of oncologic surgeries during the pandemic. In this study, we aimed to evaluate the safety of oncologic surgeries without preoperative COVID-19 testing in asymptomatic patients with gynaecological cancers when preoperative COVID-19 testing was not mandatory. Methodology: Patients with gynaecological cancers who were operated between March 11 to June 11 without preoperative COVID-19 testing at Hacettepe University Faculty of Medicine, Department of Obstetrics and Gynaecology were identified. These patients were followed up 6 weeks after surgery to evaluate COVID-19 related morbidity or mortality. Results: The study group consisted of 30 patients. Of these, 17 had endometrial cancer, 9 had ovarian cancer, 3 had cervical, and 1 had vulvar cancer. Mean age of patients was 58 years. Twenty-two patients (73.3%) had co-morbidities and among those 3 (10.0%) had pulmonary disease. Five patients (16.7%) were followed up in the intensive care unit postoperatively based on decision of attending anesthesiologists. Despite venous thromboembolism prophylaxis, one patient (3.3%) with ovarian cancer developed pulmonary embolism who was tested negative for COVID-19. This patient developed acute abdomen on 20th postoperative day and was subjected to re-laparotomy, but she died of cardiac arrest 3 days later. No significant morbidity or mortality was observed in remaining 29 patients (96.7%). Conclusion: During the COVID-19 pandemic, risk of surgical morbidity or mortality is not increased and oncologic surgeries may safely be performed without routine COVID-19 testing in asymptomatic cases even if they have co-morbidities. However, adequate infrastructure is crucial since postoperative intensive care unit admission is required for a significant proportion of patients. Disclosures: No potential conflict of interest to declare.